Teaching Strategies for ADHD Student in Inclusive Classroom: A Case Study - Dewi Nurlyan Purwita; Bibit Suhatmady; Iwan Setiawan; Weningtyas Parama Iswari; Effendi Limbong; Ichi Ahada; Leilanie B. Queja (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background: Every student with special needs must be recognized for their right to get an education that is equal to regular students. In order to overcome the learning difficulties that ADHD students face when learning English in regular classrooms with other students, this study expects to analyze the strategies for teaching that English teacher has particularly implemented. Methodology: This study uses qualitative research design, specifically a case study of an English teacher in Samarinda who teaches a seventh-grade ADHD student. Data was collected through observation and interviews, and the study used data reduction, display, and verification techniques. The credibility test using triangulation was used to verify the validity of the data. Findings: Teacher strategies for teaching a student with ADHD at an inclusive junior high school in Samarinda such as repetition of material, direct instruction, indirect instruction, giving reward, and classroom accommodation. Conclusion: Teaching strategies used by the English teacher to a student with ADHD only a classroom accommodation. There are also some strategies used not only to a student with ADHD but also to regular students which are, repetition of material, direct instruction, indirect instruction, giving reward. Originality: Previous studies have explored the strategies used by teachers in teaching students with ADHD in general. However, there is a gap in this study, which explores the strategies used by English teacher in teaching an ADHD student in regular classroom.